2012
DOI: 10.1016/j.bbapap.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of host cellular proteases in the pathogenesis of influenza and influenza-induced multiple organ failure

Abstract: Influenza A virus (IAV) is one of the most common infectious pathogens in humans. Since the IVA genome does not have the processing protease for the viral hemagglutinin (HA) envelope glycoprotein precursors, entry of this virus into cells and infectious organ tropism of IAV are primarily determined by host cellular trypsin-type HA processing proteases. Several secretion-type HA processing proteases for seasonal IAV in the airway, and ubiquitously expressed furin and pro-protein convertases for highly pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 57 publications
0
127
0
Order By: Relevance
“…Furthermore, H5N1 was able to spread efficiently to nonrespiratory tissues, such as the brain and kidney, while H7N9 was only transiently detected in these tissues, if at all. Highly pathogenic H5N1 viruses possess a multibasic cleavage site and are able to utilize ubiquitous cellular proteases such as furin, which accounts for an efficient spread throughout the alveolar space leading to the systemic spread seen with H5N1 viruses (27). However, H7N9 viruses were able to spread efficiently throughout the alveoli at later points in infection.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, H5N1 was able to spread efficiently to nonrespiratory tissues, such as the brain and kidney, while H7N9 was only transiently detected in these tissues, if at all. Highly pathogenic H5N1 viruses possess a multibasic cleavage site and are able to utilize ubiquitous cellular proteases such as furin, which accounts for an efficient spread throughout the alveolar space leading to the systemic spread seen with H5N1 viruses (27). However, H7N9 viruses were able to spread efficiently throughout the alveoli at later points in infection.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of cleavage on signaling activation is a matter of open discussion: while it was seen by some laboratories to be a prerequisite for delivery of receptors to the cell surface [84,85], other groups have shown that Notch receptors which are defective for S1 cleavage are normally exposed to the cell surface, but fail in ligand-mediated activation of canonical Notch signaling [86,87]; these latter data support the hypothesis that dissociation of NECD from NTMD (by endocytosis, see later) may be a prerequisite for S2 proteolysis. Notably, S1 cleavage-defective Notch receptors exhibit little change in their crystal and NMR structure in comparison with wild-type receptors [88]; this is in contrast to what happens with some viruses (including avian influenza virus, HIV-1, measles and papilloma virus [89][90][91][92]) in which furin cleavage induces major conformational changes leading to protein activation (reviewed in [93]). …”
Section: Domain Structure Of Notch Componentsmentioning
confidence: 73%
“…The inflammatory response also affected cell adhesion, vascular permeability, apoptosis, and mitochondrial reactive oxygen species, which could progress to vascular dysfunction and multi-organ failure. Studies have shown that influenza virus infection significantly upregulates the expression of cellular trypsins and matrix metalloproteinase-9 in various organs and vascular endothelial cells (30). We propose that in addition to direct damage to alveolar epithelial cells, cytokine storm-induced endothelial cell damage and successive vascular hyperpermeability play major roles in the pathogenesis of severe influenza virus-induced pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus infection caused marked increases in the levels of pro-inflammatory cytokines, tumor necrosis factor-α, interleukin (IL)-6, and IL-1β (cytokine storm) (30). The inflammatory response also affected cell adhesion, vascular permeability, apoptosis, and mitochondrial reactive oxygen species, which could progress to vascular dysfunction and multi-organ failure.…”
Section: Discussionmentioning
confidence: 99%